The use of microtracers in food‐effect trials: An alternative study design for toxic drugs with long half‐lives exemplified by the case for alectinib - L. T. van derHeijden; N. Steeghs; J. H. Beijnen; A. D. R. Huitema; T. P. C. Dorlo (Wiley, 2023)
Abstract The traditional design of food‐effect studies has a high patient burden for toxic drugs with long half‐lives (e.g., anticancer agents). Microtracers could be used to assess food‐effect in patients without influencing their ongoing treatment. The feasibility of a microtracer food‐effect study during steady‐state of the therapeutic drug was investigated in an in silico simulation study with alectinib as an example for a relative toxic drug with a long half‐life. Microtracer pharmacokinetics were simulated based on a previously published population pharmacokinetic model and used for estimation of a model with and a model without food as a covariate on oral bioavailability of alectinib (assuming a 40% food‐effect). Power was defined as the fraction of clinical trials where a significant (p < 0.01) food‐effect was identified. The proposed study design of 10 patients on steady‐state treatment, 10 blood samples collected within 24 h after administration and an assumed food‐effect of 40% had a power of 99.9%. The mean estimated food‐effect was 39.8% (80% confidence interval: 31.0%-48.6%). The feasibility of microtracer food‐effect studies was demonstrated. The design of the microtracer food‐effect study allowed estimation of the food‐effect with minimal influence on therapeutic treatment and reducing patient burden compared to the traditional study design for toxic drugs with long half‐lives.